Revision of demand theory - "Hicks, J.R." (Oxford, 1956)
The demand theory which Iam revising in this book is that of the first three chapters of my Value and CapitaL. I have felt that this theory does need some reconsideration, in the light of the work which has been done during the seventeen years which have elapsed since it was first published. I can nevertheless maintain that the original version stands up to the revision pretty well. I do not now think that the methodology was quiite as it should have been; some of the treatment was too elliptic, and some difficulties. which deserved more serious attention, were brushed aside; most important of all, some opportunities were missed.
Keywords: Demand (Economic theory)